Dynamic trading indicators : - Helweg, Mark W. (J. Wiley, 2002)
The authors have introduced a new idea in charting–the Value Chart. Their expertise in technical analysis and in designing and testing trading systems around this new charting concept makes this book a must- read for all stock and futures traders."